STRATEGI PROMOSI SHIROKUMA CAFE DI MASA PANDEMI - Sofi Ani (Jurnal Hospitality dan Pariwisata, 2021)
The COVID-19 pandemic caused a significant effect for many economic sectors, especially the food and beverage industry. Many companies in this field are forced for either temporary or permanent closure. This study was conducted to find out what kind of promotional strategies done by Shirokuma Cafe during the pandemic to attract customers. This qualitative research was done by collecting data by interviewing, observing, as well as documenting the data gathered from both the head office as well as employees of Shirokuma Cafe. This study shows that promotional activities carried out by Shirokuma Cafe during the pandemic are sales promotion, and advertising that utilizes social media, namely Instagram, as well as direct marketing using SMS and whatsapp inform customers about their latest on going promos. These promotional strategy activities are effective in increasing sales at Shirokuma Café. Promotional activities that are not used by Shirokuma Cafe are personal sales and public relations activities due to unsupportive circumstances and budget. Shirokuma Café's promotional strategies such as sales promotion, advertising, and direct marketing focus on social media. In order to attract customers, Shirokuma Cafe can often hold activities such as holding seminars, giveaways, and collaborating with food bloggers to introduce their products to the public.